Strengthening Islamic Literacy in Education: A Literature Review for Cultivating Intelligent Muslims in the Modern Era: - Ahmad Mubaidilah; Sabihis Sabihis; Hawwin Huda Yana (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Strengthening Islamic literacy in education is crucial in today's digital age, given the role of technology in influencing religious understanding. This research aims to explore how Islamic literacy can be applied in education to shape a generation of intelligent and virtuous Muslims. This research employs a literature review method, analyzing various literature sources related to Islamic literacy in the context of education. The results of the study indicate that Islamic literacy is not only about religious understanding but also includes the development of critical and ethical thinking skills, which are highly relevant to the challenges of the times. Strengthening Islamic literacy is expected to improve the quality of education and help students be better prepared to face social and technological challenges. The implication of this research is the importance of developing an Islamic literacy-based curriculum and using technology wisely in education, while maintaining religious values. This research also opens opportunities for further research on the practical impact of implementing Islamic literacy in education.